Acute Effects of High-Intensity Interval Running on Lower-Body and Upper-Body Explosive Strength and Throwing Velocity in Handball Players. Issue 11 (25th November 2022) - Seipp, Deborah; Feuerbacher, Joshua F.; Jacobs, Mats W.; Dragutinovic, Boris; Schumann, Moritz
Abstract: Seipp, D, Feuerbacher, JF, Jacobs, MW, Dragutinovic, B, and Schumann, M. Acute effects of high-intensity interval running on lower-body and upper-body explosive strength and throwing velocity in handball players. J Strength Cond Res 36(11): 3167–3172, 2022—The purpose of this study was to determine the acute effects of handball-specific high-intensity interval training (HIIT) on explosive strength and throwing velocity, after varying periods of recovery. Fourteen highly trained male handball players (age: 25.4 (26.2 ± 4.2) performed HIIT consisting of repeated 15-second shuttle runs at 90% of final running speed (VIFT ) to exhaustion. Upper-body and lower-body explosive strength and throwing velocities were measured before and immediately after HIIT, as well as after 6 hours. These tests included 3 repetitions of both bench press and squat exercise at 60% of the 1 repetition maximum (1RM) as well as 3 repetitions of the set shot without run up and jump shot, respectively. Explosive squat performance was significantly reduced at post (−5.48%, p = 0.026) but not at 6 h (−0.24%, p = 1.000). Explosive bench press performance remained statistically unaltered at post (0.32%, p = 1.000) and at 6 hour (1.96%, p = 1.000). This was also observed in the subsequent throws both immediately after (−0.60%, p = 1.000) (−0.31%, p = 1.000) and at 6 h (−1.58%, p = 1.000) (1.51%, p = 0.647). Our data show a reduction in explosive strength of the lower but not upper extremities when preceded by running HIIT. Since throwing velocity was not affected by intense lower-body exercise, combining lower-body HIIT and throwing practice may be of no concern in highly trained handball players.